A Comparison of the Clinical and Epidemiological Profile of Rocky Mountain Spotted Fever with Dengue and COVID-19 in Hospitalized Children, Sonora, México, 2015–2022 - Gerardo Álvarez-Hernández; Cristian Noé Rivera-Rosas; Jesús René Tadeo Calleja-López; Jehan Bonizú Álvarez-Meza; Maria del Carmen Candia-Plata; Denica Cruz-Loustaunau; Antonio Alvídrez-Labrado (Tropical Medicine and Infectious Disease)
Background: Rocky Mountain spotted fever (RMSF) is a challenge for physicians because the disease can mimic other endemic febrile illnesses, such as dengue and COVID-19. The comparison of their main clinical and epidemiological manifestations in hospitalized children can help identify characteristics that improve empirical suspicion and timely therapeutic interventions. Methods: A cross-sectional study was conducted on a series of patients aged 0 to 18 years, hospitalized between 2015 and 2022, with a diagnosis of RMSF, dengue, or COVID-19. Data were retrieved from medical records. Subjects were categorized as patients with RMSF (group I) and patients with dengue and COVID-19 (group II). Descriptive statistics were used, and differences were evaluated using Student’s t-test and the chi-squared test. Results: A series of 305 subjects were studied, with 252 (82.6%) in group I. Subjects in both groups presented fever, myalgias, arthralgias, and rash, but exposure to ticks distinguished group I. The fatality rate (21.0%) in group I was higher than in group II (3.8%). Conclusions: Although fever, myalgias, arthralgias, and rash are common in all three illnesses, they are more prevalent in hospitalized patients with RMSF. In the presence of such symptoms, a history of tick exposure can guide clinical decisions in regions where all three diseases are endemic.